Securiing VOIP : keeping your VOIP network safe - Bates, Regis J. (Bud) (Waltham : Elsevier, 2015)
Securing VoIP: Keeping Your VoIP Network Safe will show you how to take the initiative to prevent hackers from recording and exploiting your company$1 (Bs secrets. Drawing upon years of practical experience and using numerous examples and case studies, technology guru Bud Bates discusses the business realities that necessitate VoIP system security and the threats to VoIP over both wire and wireless networks. He also provides essential guidance on how to conduct system security audits and how to integrate your existing IT security plan with your VoIP system and security plans, helping you prevent security breaches and eavesdropping.s
Index 199-207p.
Keywords: Authentication; Final thoughts; Cryptography solutions